The individual factors influencing the work-life balance of nurses and midwives at Mukono Church of Uganda Hospital. A cross-sectional study. - Mugenyi, Grace Ketra; Mayanja , Edrine; Naggulu, Immaculate; Nansereko, Hasifa; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background The study aimed to identify the individual factors influencing the work-life balance of nurses and midwives at Mukono Church of Uganda Hospital. Methodology A descriptive cross-sectional study was conducted among 32 nurses and midwives at Mukono Church of Uganda Hospital using purposive sampling. Data were collected via self-administered questionnaires, both electronic and face-to-face, covering demographic, individual, and health facility-related factors affecting work-life balance. Data were analyzed using descriptive statistics in Excel and thematic analysis for interviews. Validity and reliability were ensured through expert review and a pilot study. Ethical approval, informed consent, and confidentiality were strictly maintained throughout the study. Results Among the 32 respondents, most were aged 25–34 years (42.7%) and female (68.7%). The majority were married (53.1%) with 1–2 dependents (43.7%) and had 6–10 years of work experience (34.4%). Midwives represented 53.1% of the sample, while nurses represented 46.9%. Regarding work-life balance, 40.6% reported being unable to balance work and family duties at all, whereas 9.4% balanced easily. Emotional effects sometimes influenced work-life management for 37.5%, while 15.6% reported no effect. Fatigue due to work and family demands affected 31.3% strongly, and 21.9% were neutral. Most respondents (40.6%) had limited personal time, 28.1% rarely had time, and 21.9% had no personal time. Family support was not supportive for 43.7%, somewhat supportive for 28.1%, and very supportive for 21.9% of respondents. Conclusion Nurses and midwives at Mukono COU Hospital struggle with work-life balance due to heavy workloads, fatigue, limited personal time, and insufficient support. Recommendation Hospitals should improve staffing, shift management, and support systems, while staff should seek family support and practice self-care to enhance work-life balance.